Factors Affecting Patient Safety By Nurses In Medan - Sontina Saragih (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Patient safety is a system that makes care safer, including risk assessment, identification and management of patient risks, reporting, incident analysis, the ability to learn from incidents and follow up, implementation of solutions to minimize risks and prevent injuries caused by errors resulting from carry out an action or take action that should be taken. This study aims to determine the factors that influence the implementation of patient safety by nurses at Hospital X in Medan. The type of research used is quantitative research with a cross sectional approach. The population in this study were 85 inpatient nurses at Hospital X in Medan. The number of samples in the study was 75 respondents according to the criteria, using the total sampling technique. The statistical test used is the Chi Square Test. The results of the research show that there is a relationship between nurses' knowledge (p-value=0.004), Hospital Organization/Management (p- value=0.030) and the implementation of patient safety by nurses at Hospital in Medan. Increasing the knowledge and skills of nurses' performance by holding training regularly and continuously, Create organizational policies by implementing a punish and reward system for nurses according to their performance.